(untitled) (Revista Internacional de Folkcomunicação, 2018)
ABSTRACT The close relationship between media, tourism and popular culture expanded the view of Luiz Beltrão’s disciples, who from Folkcommunication, a genuinely Brazilian theory, observed the appropriation of cultural assets as tourist attractions through means of information and communication. Elements of local production as cultural, religious and gastronomic manifestations start to become salable products that impact mainly on the economy of the region. Thus, this research is based on pointing out the Queijada de Dona Marieta as a folkturistico element in the city of São Cristóvão, as a strategy for local development. The contribution of this debate is to strengthen the recognition of the Beltranian theory, as well as to expand the eyes of the disciples of Luiz Beltrão. KEY-WORDS Folkturismo; Queijadinha; São Cristóvão; Tourism.